2018
DOI: 10.3390/v10080399
|View full text |Cite
|
Sign up to set email alerts
|

The Accessory Protein ORF3 Contributes to Porcine Epidemic Diarrhea Virus Replication by Direct Binding to the Spike Protein

Abstract: The porcine epidemic diarrhea virus (PEDV) is an important swine pathogen responsible for severe watery diarrhea, particularly in neonatal piglets. Despite extensive studies performed to elucidate the function of several viral proteins, the contribution of an accessory protein ORF3 in PEDV replication is still largely unknown. Here, we constructed expression plasmids as well as recombinant PEDV carrying myc-tagged ORF3 to assess their expression and subcellular localization in both transfected and infected cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 22 publications
2
42
0
Order By: Relevance
“…In our study, we firstly constructed different eukaryotic expression vectors to expression ORF3 protein, and found ORF3 protein distributed in perinuclear cytoplasm, and then shifted for aggregation and concentrated in the nucleate of cytoplasm to form punctate patter. This distribution manner of PEDV ORF3 is similar with one study that ORF3 proteins localizes in the cytoplasm in punctate manner (Ye et al, 2015), but distinguishes from the other report of uniform distribution in cytoplasm diffusely (Wongthida et al, 2017;Kaewborisuth et al, 2018). We speculate that the localization and distribution manner of PEDV ORF3 might be dependent on the virus strain-type-specific differences.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In our study, we firstly constructed different eukaryotic expression vectors to expression ORF3 protein, and found ORF3 protein distributed in perinuclear cytoplasm, and then shifted for aggregation and concentrated in the nucleate of cytoplasm to form punctate patter. This distribution manner of PEDV ORF3 is similar with one study that ORF3 proteins localizes in the cytoplasm in punctate manner (Ye et al, 2015), but distinguishes from the other report of uniform distribution in cytoplasm diffusely (Wongthida et al, 2017;Kaewborisuth et al, 2018). We speculate that the localization and distribution manner of PEDV ORF3 might be dependent on the virus strain-type-specific differences.…”
Section: Discussionsupporting
confidence: 85%
“…However, there are lack of reports about the influence of PEDV ORF3 on the ER stress, apoptosis and autophagy. Up to date, the investigation of ORF3 is hampered by difficulty of detecting protein expression (Kaewborisuth et al, 2018). Thus in present study, we initiated the construction of various recombinant plasmids expressing PEDV ORF3 protein fused with different tags, and found ORF3 localized in the cytoplasm in the aggregation manner.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Interestingly, constitutive expression of the ORF3 protein exerted a positive regulatory effect on the proliferation of attenuated PEDV but not on that of virulent PEDV [17]. In a more recent study, both the wild type and a mutant ORF3 protein lacking residues 82-98 were found to co-localize with the S protein intracellularly and at the cell surface, both in infected cells and during co-expression in transfected cells [18]. Additionally, a direct interaction of the S protein with each of these ORF3 proteins was demonstrated in such transfected cells by co-immunoprecipitation, leading the authors to suggest that the ORF3 protein might be involved in virus assembly.…”
Section: Introductionmentioning
confidence: 95%
“…Using a similar strategy, Fan et al developed an infectious cDNA clone for a Chinese PEDV variant strain, AH2012/12 (Fan et al, 2017). Li et al developed a reverse genetics system for two Chinese PEDV strains with differing virulence by ligation of cDNA fragments into BACs one by one (Li et al, some PEDV proteins, such as S protein and ORF3, in modulating PEDV pathogenicity have been examined (Beall et al, 2016;Hou et al, 2017Hou et al, , 2019Kaewborisuth et al, 2018;Wang et al, 2018). Several recombinant PEDV vaccine candidates have also been generated using reverse genetics systems (Hou et al, 2019;Kao et al, 2018;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%